Stigma Among People Living With Aids (PLHIVs) in Iligan City - Porras, Marph Daryl; Labadisos, Renebel; Mendoza, Myrma Jean (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2019)
Alarmed with the rapid increase of HIV cases in the Philippines, the government has instituted Republic Act 8504 known as Philippine AIDS Prevention and Control Act of 1998. Down south, an ordinance on policies and measures to prevent and control STI, HIV/AIDS infections was promulogated in Iligan City. A non-government organization, known as Northern Mindanao AIDS Advocates (NorMAA) was organized to extend assistance to People Living with HIV (PLHIV) in the area by providing emotional recovery in terms of acceptance of their condition. With a very scarce if not nil local literature on PLHIV, it necessitates the conduct of this study. Conducted in Iligan City, the study aims to find out social stigma and coping mechanisms among PLHIV members of the NorMAA. Using a qualitative design of key informant interviews which entails an in-depth interview, the study conducted a personal and individual interview with seven informants who were identified purposively using a snowball or referential sampling method. Research ethics of informed consent and confidentiality are strictly observed by the researchers in the conduct of data gathering and data presentation. Findings were analyzed using the social stigma of Erving Goffman (1963) and the social identity of Tajfel (979). Labeled as Person Living with HIV (PLHIV) and having joined the NorMAA, the key interview informants acquired the social identity as PLHIV. With such identity and dreaded health conditions, two courses of action are found among the informants: disclosure and concealment of their social identity and health status as PLHIV. Those who disclosed their identity to their significant others had negative experiences which to them are a stigma. Those who preferred to conceal their identity as PLHIV attributed this to imagined stigma – forms of stigma which they imagined to experience once their health status is known by others. Various forms of assistance from the government and NGOs like the NorMAA help the PLHIV cope with their health conditions. Despite their stigmatized social identity, most PLHIV maintained a positive outlook in life with better perceived life chances.